Study guides

☆☆

Q: Factor ab plus 3a plus b2 plus 3b?

Write your answer...

Submit

Still have questions?

Related questions

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

(a + 3)( b + 2)

The GCF is a.

(b + 3)(a + c)

0

a(3+b)+c(3+b) * * * * * This is easy to finish: . . . = (a + c)(3 + b).

The factors of 3a are 3 and a. The factors of 6c are 6 and c. The factors of ab are a and b.

That factors to (b + 3)(a + c)

ab + 2a + 3b + 6

so let's group and then factor ab+2a+3b+6= (ab+2a)+(3b+6)= a(b+2)+3(b+2)= (a+3)(b+2) and that is our final answer! Doctor Chuck

(a - 2)(b + 3)

ab-2ac+b^2-2bc

People also asked

Featured Questions